'I Too Am a Human': The Political Psychology of Pakistan's Former President General Pervez Musharraf. (September 2019) - Conley, Ross F.
This study explores the political psychology of General Pervez Musharraf, Pakistan's most recent military dictator. It categorises his 'operational code'—a collection of general political beliefs assessed from spoken and/or written statements—over four periods of his nine years of power. By analysing word choices in 55 interviews and press conferences, the findings suggest that Musharraf maintained stable beliefs of a friendly political universe and a preference for cooperative strategies to achieve his goals. The largest changes in his beliefs came immediately after 9/11. Before, Musharraf expressed his strongest beliefs of a friendly political universe and favour for cooperation. After 9/11, these beliefs decreased, but they remained overall friendly and cooperative. Additionally, 9/11 appears to have had the largest influence on Musharraf's beliefs on how he should operate to meet his goals (instrumental beliefs), not on his beliefs of others in the political environment (philosophical beliefs). Applied today, this can be useful when engaging Pakistan's leaders. With Musharraf as an example, the long-held, philosophical beliefs of Pakistan's leaders may not easily change. Foreign officials may find more success accepting these beliefs and focusing on shared goals that align with Pakistan's political worldview.